2007
DOI: 10.3201/eid1312.070730
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Local Anthropogenic Changes on Potential Malaria VectorAnopheles hyrcanusand West Nile Virus VectorCulex modestus,Camargue, France

Abstract: Sixty years of environmental modifications have led to strong and rapid effects on the abundance of vector populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…For instance, a study investigating a region in France from World War II to 1971 found that the populations of An. Hyrcanus , a vector with potential for malaria transmission, and of the West Nile Virus vector Culex modestus were initially very high in agricultural areas, decreasing after a few years owing to pesticide control in rice cultivation (Ponçon et al 2007). However, a number of factors caused the population of theses mosquitoes to increase again in 2000, raising the risk of malaria and WNV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study investigating a region in France from World War II to 1971 found that the populations of An. Hyrcanus , a vector with potential for malaria transmission, and of the West Nile Virus vector Culex modestus were initially very high in agricultural areas, decreasing after a few years owing to pesticide control in rice cultivation (Ponçon et al 2007). However, a number of factors caused the population of theses mosquitoes to increase again in 2000, raising the risk of malaria and WNV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, deforestation was shown to have an impact on the biting rate of malaria vectors in South America (Vittor et al, 2006), and anthropogenic land use changes are associated with altered abundance of mosquito vectors for West Nile virus and malaria in France (Poncon et al, 2007). However, the studies focused on mosquito abundance rather than virus or parasite prevalence in the vectors.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of changes in driver 3 led to unexpected results because the vector species in the Camargue has changed through history. Until the early 20th century, Anopheles atroparvus was the main malaria vector in the Camargue (Rodhain and Charmot, 1982;Ponçon et al, 2007c). Nowadays, this competent vector species became rare, whereas An.…”
Section: Discussionmentioning
confidence: 97%